Germline genetics in localized prostate cancer. Issue 4 (July 2019) - Ryan, Stephen T.; Nguyen, Vi; Bree, Kelly K.; Holst, Daniel D.; Kader, A. Karim
Abstract : Purpose of review: To provide the reader an understanding of the importance and limitations of prostate cancer (PCa) screening, the heritable component of PCa and the role that germline genetic markers can play in risk-adapted screening and treatment. Recent findings: Despite strong science supporting the association of germline genetic change with PCa risk and outcome, there has been a reluctance to pursue practical application of these technologies. Recent findings suggest that actionable information may now be garnered from this form of testing, which can help men at risk for and with PCa. Summary: This is an exciting time whereby germline genetic markers can help overcome some of the shortcomings of current PCa screening and treatment paradigms. Understanding their benefit and limitations while keeping the patient's best interest in mind will be the key for the responsible application of these exciting technologies.